Modulating ascorbic acid levels to optimize somatic embryogenesis in Picea abies (L.) H. Karst. Insights into oxidative stress and endogenous phytohormones regulation - Hazubska-Przybył, Teresa; Obarska, Agata; Konecka, Agata; Kijowska-Oberc, Joanna; Wawrzyniak, Mikołaj Krzysztof; Piotrowska-Niczyporuk, Alicja; Staszak, Aleksandra Maria; Ratajczak, Ewelina (Frontiers in Plant Science, 2024)
Global warming has adversely affected Picea abies (L.) H. Karst. forests in Europe, prompting the need for innovative forest-breeding strategies. Somatic embryogenesis (SE) offers promise but requires protocol refinement. Understanding the molecular mechanisms governing somatic embryo development is essential, as oxidative stress plays a crucial role in SE regulation. Ascorbic acid (ASA), is a vital antioxidant that can potentially control oxidative stress. In the present study, we normalized ASA concentrations in induction and proliferation media to enhance embryogenic tissue (ET) regeneration and proliferation capacity of mature explants. The media were supplemented with ASA at 0 mg l−1, 25 mg l−1, 50 mg l−1, 100 mg l−1, and 200 mg l−1. The accumulation of hydrogen peroxide (H2O2) and endogenous phytohormones, including auxins, cytokinins, brassinosteroids, abscisic acid, and gibberellin, was measured in non-embryonic calli and ET. Subsequently, their impact on ET induction and multiplication was analyzed. Our results demonstrate that application of ASA at concentrations of 25 mg l−1 and 200 mg l−1 led to increased H2O2 levels, potentially inducing oxidative stress while simultaneously reducing the levels of all endohormone groups. Notably, the highest ET induction frequency (approximately 70%) was observed for ASA at 50 mg l−1. These findings will enhance SE induction procedures, particularly in more resistant explants, underscoring the significance of ASA application to culture media.